Estudio clínico controlado, comparación y réplica de una intervención para abusadores de narcóticos en Delhi, India. - Gómez, Juan Daniel; Cand, Phil; Kaplan, Charles D. (Acta Colombiana de Psicología, 1998)
The behaviour which is established in an extreme way, under the control of external agents, can be treated through behavioural-cognitive therapeutic procedures (Rotter. 1954: Ellis, 1962; Bandura, 1969; Kanfer, 1971: Mahoney, 1974: Kanfer and Grintm, 1980: Di Clemente & Prochaska, 1985, among others),being advisable,in some cases, its combination with pharmacotherapeutic coadjuvants (Dorabjee, J., Samson, L., Kaplan, Ch.D., & Wodak, A., 1994).The principle demostrated by the first authors, is mainly applicable to the treatment for abuse of inhaled, for oral use, and injecting drugs, and the effectiveness of its combination with pharmacotherapeutic technics exclusively, for injecting drug users (IDUs or EsDI in Spanish language), pretends to be demostrated in this present study.The addiction to psychoactive substances can be proposed as a model of conduct which is not only determined by stimulus from the environment,but that is also subjected to the individuals own control. Self-reflection and self determination are qualities of the individual's that can play an important role in the procedures of the behaviour therapy. In this context, the therapeutic concept of behavioural self-control has an important meaning (Eeldhegc, 1977; Eeldhege. 1980). Self-control, self-help, self-regulation,and self-control therapy directed towards clients addicted to drugs, serve for achieving the objective of regulating the drug ingesting behaviour, in such a way that the frecuency and intensity of the problematic behaviour may significantly diminish. The study’s is being applied. It will take advantage of an unpublished model of controlled study that combines three different procedures of self-control in order to treat those who abuse of psychoactive substances (SPAs),and of the reply of a substitutive pharmacotherapeutic procedure for UsDI They are: a) technics that are based on different sections of the model of work proposed by Kanfer in 1971 (self-observation, self-commitment, self-evaluation, selfreinforcement and self-punishment): b) procedures of covcrant conditionings) methods belonging to the cognitive therapy, conceived on Mahoney's sense; Ulrich & Ulrich’s social training (1973); and d) the substitutive therapy procedure for those who abuse of narcotics, by using Dorabjee, Samson, Kaplan & Wodak’s 1994 study (see Appendix A).